Respuesta :
Answer:
23.64
Step-by-step explanation:
[tex]\frac{6.6+3.2}{5}[/tex] × (2 - 5)² + 6
= [tex]\frac{9.8}{5}[/tex] × (- 3)² + 6
= 1.96 × 9 + 6
= 17.64 + 6
= 23.64
The value of the (6.6 + 3.2)/5*(2-5)²+6 is 23.64
What is expression?
An expression is a set of terms combined using the operations +, -, x or ÷, /
Given statement:
The sum of 6.6 and 3.2 all divided by 5 times the quantity of the squared difference of 2 minus 5 plus 6.
Now,
(6.6 + 3.2)/5*(2-5)²+6
=9.8/5*3²+6
=1.96*9+6
=17.64+6
=23.64
Hence, the value is 23.64.
Learn more about expression here:
https://brainly.com/question/24242989
#SPJ2